Kingdom of Lesotho : Requests for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for the Kingdom of Lesotho. (IMF Staff Country Reports; Country Report, 2020)
The COVID-19 pandemic is having a severe impact on Lesotho's economy. Supply chains for major industries have been disrupted and a national shutdown to contain the virus curtailed economic activity with adverse social impacts. The economy is expected to be further hit by declining external demand for textiles and diamonds, shrinking remittances, and delays to major construction projects. The authorities are taking measures to contain the virus and are implementing plans to mitigate its health and economic consequences. The economic shock, as well as the additional required spending, have generated urgent balance-of-payments (BOP) needs. Lesotho does not have an arrangement with the Fund.